Endodontic management of a mandibular incisor with severe canal obliteration: a case report - Valverde Haro, Henry Paul (2025)
One of the physiological procedures associated with injuries to the dental pulp is root canal obliteration, characterized by partial or total narrowing of the canal, making its access or localization challenging. With today’s technology, digital planning of the access cavity, using minimally invasive techniques through CBCT and intraoral scanning of the patient’s mouth, improves this complex clinical situation. This case involves a 66-year-old patient with dyschromia of the lower central incisor, a history of dental trauma, and a positive response to percussion testing, with pulp necrosis and symptomatic apical periodontitis. A three-dimensional impression of an endodontic access guide was made. The root canal was then permeabilized in a controlled manner and the canal was located using a minimally invasive approach. The root canal was treated conventionally. Clinical and radiographic follow-up after one year demonstrated the effectiveness of using a static guide for endodontic treatment in cases of severe obliteration.